Pengaruh Keterlibatan, Motivasi dan Komitmen Kerja terhadap Kepuasan Kerja Karyawan di PT. CIMB NIAGA FINANCE - Arafah, Nabila Rizqi; Fauzan, Mohammad (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze and explain (1) the effect of work engagement on job satisfaction, (2) the effect of work motivation on job satisfaction, (3) the effect of work commitment on the job satisfaction of employees of PT. CIMB Niaga Finance. This research is a type of explanatory research. The research sample was 100 people. The data collection technique uses a questionnaire distributed through google forms. Data analysis uses multiple linear regression with the help of SPSS software. The results of the study showed that (1) work engagement had a positive effect on job satisfaction (2) work motivation had a positive effect on employee job satisfaction (3) work commitment had no effect on employee job satisfaction of PT. CIMB Niaga Finance.